2014
DOI: 10.1016/j.coviro.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Roseoloviruses in transplant recipients: clinical consequences and prospects for treatment and prevention trials

Abstract: Roseoloviruses frequently reactivate in transplant recipients. We review the impact of Roseoloviruses in transplant recipients and highlight research priorities. Human herpesvirus 6A (HHV-6A) and HHV-6B were recently classified as distinct species with important differences. Both viruses can result in inherited chromosomally integrated HHV-6, which may cause complications after transplant. HHV-6B is the primary species associated with disease and appears to have pleiotropic effects on the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 70 publications
1
44
0
1
Order By: Relevance
“…1). Binding of 1H6 antibodies to G-rich oligonucleotides [(TTAGGG) 4 ] was also observed. Marginal binding to the singlestranded DNA (ssDNA) was recorded, as previously reported (41,42).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…1). Binding of 1H6 antibodies to G-rich oligonucleotides [(TTAGGG) 4 ] was also observed. Marginal binding to the singlestranded DNA (ssDNA) was recorded, as previously reported (41,42).…”
Section: Resultsmentioning
confidence: 92%
“…To ensure the correct folding of oligonucleotides into G-quadruplex structures, we initially performed an enzyme-linked immunosorbent assay (ELISA) using the BG4 and 1H6 antibodies that specifically bind to G-quadruplex structures. We demonstrated that the BG4 antibodies preferentially bind G-rich oligonucleotides, such as the telomeric [(TTAGGG) 4 ] and myc oligonucleotides. The latter corresponds to a DNA sequence present in the promoter of the MYC gene and was previously reported to fold into a G-quadruplex structure (38)(39)(40) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 HHV-6B reactivation based on DNA detection in serum or plasma occurs in 30% to 50% of allogeneic hematopoietic cell transplant (HCT) recipients, is the most frequent cause of infectious encephalitis, and is associated with acute graft-versus-host disease (GVHD), cytopenias, cytomegalovirus (CMV) reactivation, and increased overall mortality. 3 The epidemiology and clinical consequences of HHV-6A are less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This has been associated with complications, such as central nervous system dysfunction, fever and rash, myelosuppression, graft rejection, and acute graft-versus-host disease (GVHD), some of which have also been reported after solid organ transplantation (8). While further research is needed to determine the clinical significance of inherited ciHHV-6A or -B after transplantation, it is well recognized that inherited ciHHV-6A or -B complicates molecular diagnostic testing for HHV-6B reactivation (9,10).…”
mentioning
confidence: 99%